The Dream Society: The Coming Shift from Information to Imagination - Rolf Jensen (New York McGraw Hill, 1999)
The future is uncertain -- the world is constantly changing. While anything can happen, some things are far more likely than others. Rolf Jensen, internationally renowned futurist, provides readers with a tangible look at what the future will be like over the next 25 years.By identifying what lies ahead, Jensen gives people the knowledge they need to make informed decisions and strategically align themselves to capitalize On the unknown future, a future Jensen calls "the Dream Society". This dream society is characterized by the commercialization of emotions. In this provocative exploration. Jensen says that it will no longer be enough to produce a useful product. He shows that, to be successful, the primary purpose of a product will be the ability to fulfill an emotional need. Those who understand the workings of this dream society will be the ones who create the new products, new markets, and new businesses that dominate the world of tomorrow.
Age Group: Adult
Includes bibliographical references (p. 223-230) and index.
Keywords: Business; Management; Business forecasting; Forecasting; Competition, International; Twenty-first century - Forecasts